Vận dụng phương pháp dạy học dự án vào dạy học ngoại ngữ ở bộ môn Đào tạo Dự bị - Khoa Quốc tế - Đại học Quốc gia Hà Nội - Nguyen, Thi Thu Huyen (Tạp chí Khoa học và Xã hội, 2020)
Project based-learning is an effective teaching method being used widely in the world nowadays. In Vietnam, there has been an increasing interest in the application of this method among educators, lectures and teachers. However, at Department of Academic Foundations, International School, Hanoi National University , Project based-learning is not commonly applied in classrooms. Results from questionaires for lectures here revealed that although 68% of the lectures have heard about project based-learning, not so many of them are clear about the benefits as well as the procedure of the method. The majority of them (92%) would like to know more about the method and hope to have the oppotunity to apply it into teaching hours at International School. Two models of project based-learning have been introduced in this paper with the hope to make it clear to the lectures at Department of Academic Foundations at International School and to motive them to use Project based-learning more often in their process of English teaching.